Analyzing the impact of mechanical damage in the piezoelectric ceramics elements of knock sensors on the frequency characteristic - Klusáček, Stanislav; Fialka, Jiří; Havránek, Zdeněk; Skalský, Michal; Pikula, Stanislav; Šedivá, Soňa; Beneš, Petr (The International Institute of Acoustics and Vibration, 2024)
Piezoelectric ceramics have been used on a long-term basis as the active element in multiple types of sensors, in examining or performing vibration, knock effects, acoustic emission, and defectoscopy, and in ultrasonic classes. Mechanical damage, including cracks, breakage, and partial separation of the piezoceramics, can arise from the normal use of sensors in industrial applications. The defects, however, are not inspectable optically when the piezoelectric element is encapsulated inside the sensor. Accelerometers, for instance, are calibrated immediately after manufacturing and then periodically in the frequency range used. Other sensors, such as those for knock detec-tion, which are permanently fixed to a machine or engine block, are only verified before ship-ment from the manufacturer. This paper focuses on the impacts exerted by the mechanical damage or breaking of an element on the rel-evant frequency characteristics and functionality verification, also highlighting the possibilities for detecting such adverse issues. In the investigation, we examined various categories of piezo-electric elements, invariably with the most common mechanical damage that occurs during the industrial use. The defects on the piezoelements were observed in detail using an optical scan-ning microscope, and their impacts were evaluated with the frequency and the direct measure-ment methods via a d33 meter. In this context, the paper aims to define a measurement method applicable in quantifying the level of damage on an active piezoelectric element. In this context, it is also determined how the actual damage affects the output parameters of the sensor.

Piezoelectric ceramics have been used on a long-term basis as the active element in multiple types of sensors, in examining or performing vibration, knock effects, acoustic emission, and defectoscopy, and in ultrasonic classes. Mechanical damage, including cracks, breakage, and partial separation of the piezoceramics, can arise from the normal use of sensors in industrial applications. The defects, however, are not inspectable optically when the piezoelectric element is encapsulated inside the sensor. Accelerometers, for instance, are calibrated immediately after manufacturing and then periodically in the frequency range used. Other sensors, such as those for knock detec-tion, which are permanently fixed to a machine or engine block, are only verified before ship-ment from the manufacturer. This paper focuses on the impacts exerted by the mechanical damage or breaking of an element on the rel-evant frequency characteristics and functionality verification, also highlighting the possibilities for detecting such adverse issues. In the investigation, we examined various categories of piezo-electric elements, invariably with the most common mechanical damage that occurs during the industrial use. The defects on the piezoelements were observed in detail using an optical scan-ning microscope, and their impacts were evaluated with the frequency and the direct measure-ment methods via a d33 meter. In this context, the paper aims to define a measurement method applicable in quantifying the level of damage on an active piezoelectric element. In this context, it is also determined how the actual damage affects the output parameters of the sensor.
Analyzing the impact of mechanical damage in the piezoelectric ceramics elements of knock sensors on the frequency characteristic
Keywords: Piezoelectric ceramic; piezoelectric charge coefficient; d33 meter; frequency method; knock sensor; Piezoelectric ceramic; piezoelectric charge coefficient; d33 meter; frequency method; knock sensor